Navigating Challenges and Maximizing Benefits in the Integration of Information and Communication Technology in African Primary Schools - Ogenyi, Fabian Chukwudi; Eze, Val Hyginus Udoka; Ugwu, Chinyere N. (International Journal of Humanities, Management and Social Science (IJ-HuMaSS), 2023)
The integration of Information and Communication Technology (ICT) in the educational systems of both public and private primary schools in Africa has become a crucial factor in enhancing teaching and learning. This paper explores the role of ICT tools in education, including computers, interactive whiteboards, learning management systems, educational apps, online collaboration tools, television, and online assessment tools. It discusses their applications and the advantages they offer, such as fostering creativity, improving academic performance, increasing motivation and responsibility, and promoting teamwork. However, it also acknowledges the challenges associated with ICT integration, including distractions, excessive usage, exposure to false information, data theft, reduced human contact, and cyberbullying. Moreover, the paper highlights key challenges in African education, such as the lack of computer literacy among instructors, low teledensity, unstable power supply, inadequate financing, and the absence of a comprehensive ICT curriculum. It concludes by emphasizing the need for a holistic approach to ICT integration, addressing infrastructure, teacher training, curriculum development, and organizational support to realize the full potential of ICT in education especially at the Primary school level.